70.8k views
3 votes
Y = -4x – 5
y = -2x + 10 solve using substitution show work please

User Fulldump
by
6.1k points

1 Answer

5 votes

Answer:

(-
(15)/(2), 25 )

Explanation:

Given the 2 equations

y = - 4x - 5 → (1)

y = - 2x + 10 → (2)

Substitute y = - 2x + 10 into (1)

- 2x + 10 = - 4x - 5 ( add 4x to both sides )

2x + 10 = - 5 ( subtract 10 from both sides )

2x = - 15 ( divide both sides by 2 )

x = -
(15)/(2)

Substitute this value into either of the 2 equations and evaluate for y

Substituting into (2)

y = - 2(-
(15)/(2) ) + 10 = 15 + 10 = 25

Solution is ( -
(15)/(2), 25 )

User Uooq
by
6.5k points